(untitled) (ARQUISUR Revista, 2014)
The New School, Alfred Roth’s book published in 1950 allows understanding the project of modern educational space as a transcontinental scale problem in the wider dissemination of ideas of architectural culture during the first half of the twenty century. With no prejudice about aesthetic adoptions of the educational buildings he analyses, the author gives priority, over other criteria, to pedagogical variables behind the project of educational space of modernity. In this sense he managed to settle as an inescapable reference for those seeking to address the relationships between architecture and pedagogy in the dimension of its historical process.